Revealing changes in the microbiome of Symbiodiniaceae under thermal stress. (12th February 2020) - Camp, Emma F.; Kahlke, Tim; Nitschke, Matthew R.; Varkey, Deepa; Fisher, Nerissa L.; Fujise, Lisa; Goyen, Samantha; Hughes, David J.; Lawson, Caitlin A.; Ros, Mickael; Woodcock, Stephen; Xiao, Kun; et al.
Summary: Symbiodiniaceae are a diverse family of marine dinoflagellates, well known as coral endosymbionts. Isolation and in vitro culture of Symbiodiniaceae strains for physiological studies is a widely adopted tool, especially in the context of understanding how environmental stress perturbs Symbiodiniaceae cell functioning. While the bacterial microbiomes of corals often correlate with coral health, the bacterial communities co‐cultured with Symbiodiniaceae isolates have been largely overlooked, despite the potential of bacteria to significantly influence the emergent physiological properties of Symbiodiniaceae cultures. We examined the physiological response to heat stress by Symbiodiniaceae isolates (spanning three genera) with well‐described thermal tolerances, and combined these observations with matched changes in bacterial composition and abundance through 16S rRNA metabarcoding. Under thermal stress, there were Symbiodiniaceae strain‐specific changes in maximum quantum yield of photosystem II (proxy for health) and growth rates that were accompanied by changes in the relative abundance of multiple Symbiodiniaceae‐specific bacteria. However, there were no Symbiodiniaceae‐independent signatures of bacterial community reorganisation under heat stress. Notably, the thermally tolerant Durusdinium trenchii (ITS2 major profile D1a) had the most stable bacterial community under heat stress. Ultimately, this study highlights the complexity of Symbiodiniaceae‐bacteria interactions and provides a first step towards uncoupling their relative contributions towards Symbiodiniaceae physiological functioning.